2020
DOI: 10.1257/aer.20171175
|View full text |Cite
|
Sign up to set email alerts
|

From Extreme to Mainstream: The Erosion of Social Norms

Abstract: Social norms, usually persistent, can change quickly when new public information arrives, such as a surprising election outcome. People may become more inclined to express views or take actions previously perceived as stigmatized and may judge others less negatively for doing so. We examine this possibility using two experiments. We first show via revealed preference experiments that Donald Trump’s rise in popularity and eventual victory increased individuals’ willingness to publicly express xenophobic views. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(120 citation statements)
references
References 37 publications
5
97
0
Order By: Relevance
“…To this point, Leonardo Bursztyn, Georgy Egorov, and Stefano Fiorin performed a series of experiments that suggested that Donald Trump’s popularity made those who were already xenophobic more comfortable expressing their xenophobic views in public. They concluded “that social norms regarding the expression of such views in the U.S. might have been causally changed by Trump’s rise in popularity and eventual electoral victory” (Bursztyn, Egorov, and Fiorin 2020, 21).…”
Section: Analysis Of Public Opinionmentioning
confidence: 99%
“…To this point, Leonardo Bursztyn, Georgy Egorov, and Stefano Fiorin performed a series of experiments that suggested that Donald Trump’s popularity made those who were already xenophobic more comfortable expressing their xenophobic views in public. They concluded “that social norms regarding the expression of such views in the U.S. might have been causally changed by Trump’s rise in popularity and eventual electoral victory” (Bursztyn, Egorov, and Fiorin 2020, 21).…”
Section: Analysis Of Public Opinionmentioning
confidence: 99%
“…Ads can alter cognitive or processing demands of acquiring information by e.g. making viewers aware of new candidates and policies (an aspect tested in DellaVigna and Kaplan, 2007), increasing the perceived salience of certain political issues (Le Pennec and Pons, 2019), or making viewers aware of the intensity of political competition or of the preferences of their peers (Bursztyn et al, 2020).…”
Section: Interpretation Of Baseline Results Within a Theoretical Frameworkmentioning
confidence: 99%
“…They also shape social values. If leader values are not desirable in the long run (e.g., xenophobia, science denial), as is the case with populist leaders (Bursztyn et al, 2020), then we will be in for a very difficult ride.…”
Section: Resultsmentioning
confidence: 99%